2007
DOI: 10.1002/j.2168-9830.2007.tb00921.x
|View full text |Cite
|
Sign up to set email alerts
|

“I Wish that I Belonged More in this Whole Engineering Group:” Achieving Individual Diversity

Abstract: Engineers need a breadth of experience to enrich the gene pool of ideas from which elegant engineering solutions can be drawn, called "individual diversity." While performing large ethnographic research studies where hundreds of engineering students were interviewed, we interviewed Inez, a student that epitomizes individual diversity. Inez is unlike most engineers: she is female, multi-minority, and from a socio-economically disadvantaged background. Inez's story is told here using "ethnography of the particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
313
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(343 citation statements)
references
References 19 publications
6
313
0
Order By: Relevance
“…This finding, which contributes to a broader conversation about what it means to be, look like, and do the work of scientists and engineers, relates to scholarship on doctoral socialization and academic professional identity development (Pifer & Baker, 2014;Sallee, 2011), and confirms the importance of mentors in the persistence of women and underrepresented faculty of color in engineering (Dutta, 2015;Foor, Walden, & Trytten, 2007).…”
Section: Social Identities and Personal Factorssupporting
confidence: 62%
“…This finding, which contributes to a broader conversation about what it means to be, look like, and do the work of scientists and engineers, relates to scholarship on doctoral socialization and academic professional identity development (Pifer & Baker, 2014;Sallee, 2011), and confirms the importance of mentors in the persistence of women and underrepresented faculty of color in engineering (Dutta, 2015;Foor, Walden, & Trytten, 2007).…”
Section: Social Identities and Personal Factorssupporting
confidence: 62%
“…1 Overcoming the "chilly" climate of engineering, 13,14 is one of the challenges facing the engineering community. Research has shown that meaningful social interactions have the potential to warm the climate, while simultaneously improving student outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Typically these efforts concentrate on the nature of the interactions and the interpersonal/intergroup dynamics. 14,[20][21][22][23] Examination at this micro-level is vital to understanding how relationships are formed, but tends to ignore the larger social structures of an environment. Examining the interaction patterns (i.e., the social structure) of students creates an understanding of how individuals are included in developing communities, "even a single time-slice of the social network of a class, which shows the social ties between the students, can reveal much about a student's position in the network."…”
Section: Introductionmentioning
confidence: 99%
“…While organizations such as the National Research Council and National Academy of Engineering communicate concerns for the increase of women and minority participation in engineering, students also need the liberty to express their individual diversity within engineering 8 . Regardless of shared ethnicity, socio-economic status, etc.…”
Section: Frameworkmentioning
confidence: 99%